The university educational challenge in the face of the COVID-19 pandemic: proposal of pedagogical criteria - Amador-Solano, María Gabriela (2022)
In Costa Rica, several studies have already reflected on the impacts of the health emergency caused by COVID-19 and remote education in higher education. However, no research has yet been found that addresses teachers as an object of study, or that is located in the context of the Technological Institute of Costa Rica (ITCR), so the motivation for this work is justified in this research gap. The purpose of this article is to propose the pedagogical criteria and the ideal competencies to teach lessons in remote education, as well as to document a case study carried out in the context of the ITCR during the years 2020 and 2021. It is argued that teachers need to use the Common Digital Competence Framework to self-assess the strengths and weaknesses in terms of their technological competence. The case study, based on qualitative research, collected data from 250 university students from Writing and Oral Communication courses through two instruments, an observation and a semi-structured online survey with open questions related to the advantages and recommendations of the use of didactic instructions, strategies and resources. Among the results obtained from the observation, the importance of didactic instruction stands out for those students with low connectivity who find it difficult to participate in the synchronous sessions. Regarding the survey, 100% of the students affirm that the use of this type of instruction guides the route that must be followed in order to build their knowledge.